Invisible decay of superdeformed states - Semmes, P. B.; Ragnarsson, I.; Berg, S. (Physical Review Letters, 1992)
In superdeformed, heavy nuclei at low spins, M1 transitions enhanced by internal conversion are expected to compete favorably with E2 rays. For strongly coupled bands with fairly large B(M1) values, the decay may proceed between the two signature partner bands with very few rays emitted. Measured E2 ray intensities may imply strict limits on the M1 strength. Experimental evidence for the M1 cross talk dominated by internal conversion is seen in superdeformed bands in Hg193.